Modifikasi Perilaku untuk Meningkatkan Kemampuan Mandiri pada Anak dengan Retardasi Mental - Hafizah Ayu Ikhwani; Endang Setianingsih (Educational Journal, 2026)
This study aimed to examine the effectiveness of behavior modification in improving independent living skills in a child with intellectual disability. A single-subject approach was employed over an eight-week intervention period involving a 10-year-old child with mild intellectual disability. The intervention incorporated behavior modification techniques, including task analysis, prompting, fading, positive reinforcement, and token economy. Data were collected through direct observation, interviews with parents and teachers, and behavioral documentation conducted before, during, and after the intervention. The findings indicated a gradual improvement in the child's ability to perform daily living activities independently, including handwashing, dressing, organizing school materials, and maintaining personal hygiene. The child also demonstrated increased initiative, self-confidence, and reduced dependence on adult assistance in both school and home environments. The consistent application of positive reinforcement and systematic reduction of prompts contributed to the maintenance and generalization of independent behaviors across different settings. These findings suggest that behavior modification is an effective intervention for enhancing adaptive functioning and independence in children with intellectual disability. Collaboration among teachers, parents, and caregivers is essential to sustain behavioral changes and promote long-term independence in everyday life.